Evelina Fue Tu Nombre / Evelina Was Your Name - Maldonado Torres, Sonia E (Radical Teacher, 2020)
On Thursday, April 18 my students and I coordinated an activity in which we celebrated the National Bilingual/Multilingual Learner Advocacy Month. In this activity, one of our adjuncts professors presented information about the struggle that a Puerto Rican woman, Evelina López Antonetty had in providing access to bilingual education to a monolingual-Spanish community in the South Bronx . The South Bronx is still considered one of the most impoverished boroughs in NYC and it is also where the college I am working at (Eugenio Maria de Hostos CC) is located. As part of the activity, I wrote a poem about Evelina López Antonetty and the poem was translated by my students into three (3) different languages.